2021
DOI: 10.1111/1346-8138.15680
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome profile in psoriatic patients treated and untreated with biologic therapy

Abstract: There are increasing data about the role of the gut microbiome in various autoimmune diseases, including psoriasis, a chronic inflammatory and immune-mediated disease. Current treatment strategies in psoriasis include immunomodulating biologic agents. A variable response to this type of therapy has been reported in psoriatic patients. A possible effect of biologic therapy on the gut microbiome composition has been suggested, but data are still limited. The aim of this study was to compare the gut microbiome co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…It has shown that acitretin inhibits the growth of Pseudomonas aeruginosa in vitro ( 47 ), which was not a common bacterium in the human intestine. Biological agents were not used in the current study due to their known impact on the composition of the gut microbiome ( 48 , 49 ). Thus, mechanistic studies with a larger sample size are needed to further explore whether acitretin has an impact on microbes.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown that acitretin inhibits the growth of Pseudomonas aeruginosa in vitro ( 47 ), which was not a common bacterium in the human intestine. Biological agents were not used in the current study due to their known impact on the composition of the gut microbiome ( 48 , 49 ). Thus, mechanistic studies with a larger sample size are needed to further explore whether acitretin has an impact on microbes.…”
Section: Discussionmentioning
confidence: 99%
“…At the species level, treated subjects had significantly higher abundances of Bacteroides plebeius , Roseburia faecis , and Bifidobacterium adolescentis , and significantly lower abundances of Bacteroides caccae , eggerthii and coprophilus , Blautia obeum , Alistipes indistinctus and massiliensis , Ruminococcus lactaris , Haemophilus parainfluenzae . The species Akkermansia muciniphila showed the highest variation in relative abundance between treated and untreated individuals [ 63 ].…”
Section: Gut Microbiome Alterations In Psoriasismentioning
confidence: 99%
“…Various therapeutic agents have been used to achieve SLE remission, such as antimalarial agents, glucocorticoids, nonsteroidal anti-inflammatory drugs (NSAIDs), immunosuppressive agents, and B cell-targeting biological agents [ 8 ]. These drugs have been found to significantly alter structure of gut microbiota [ 7 , 9 , 10 ]. Glucocorticoids may reduce the expression of inflammatory cytokines by adjusting the structure of gut microbiota in SLE patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%